Unravelling the use and sequence of regulated learning in online collaborative learning: A pilot study. - Ashrafifard, Houra; Khajavirad, Nasim; Kashani, Homa; Sandars, John; Gandomkar, Roghayeh (Medical Teacher, 2026)
Introduction: Effective online collaborative learning goes beyond completing a task. Regulating individual and group-shared learning processes is essential for success in online collaborative learning. This study had the aim of identifying how medical students use and sequence their regulation of learning during an online collaborative learning task. Methods: This study employed lag sequential analysis to examine sequential patterns of regulated learning. 68 year 4 medical students were divided into 6 groups of 11 to 12 and worked on an online prescribing scenario. Group discussions were recorded, transcribed and coded using a specifically developed coding scheme. Lag sequential analysis was then applied to identify the sequences through which different types and processes of regulated learning unfolded during the collaborative task. Results: Sequential analysis showed that medical students frequently used co-regulated learning and socially shared-regulated learning in a cyclical approach. Monitoring facilitated important metacognitive and cognitive processes and also there was an association between planning and orientation processes with positive emotions. Conclusion: The findings have implications for the design of effective online collaborative learning, such as incorporating monitoring prompts, fostering positive atmosphere in groups and providing consecutive tasks to stimulate reflection.